The Role of economic education in optimizing local resource potential to increase community income‎ - Mansyur, Fakhruddin; Hasanuddin, Hasanuddin; Abdul Malik; Fitrayani, Fitrayani (Journal of Islamic Economics Lariba, 2025)
IntroductionEconomic education plays a crucial role in empowering communities to recognize and manage the potential of local resources. In the of increasing global competitiveness, local resources are often overlooked, though they possess strategic value for community-based development. When aligned with Sharia entrepreneurial principles, the optimization of local resources can contribute not only to income growth but also to ethical and sustainable economic practices.ObjectivesThis study aims to explore the role of economic education in promoting Sharia-based entrepreneurship for optimizing local resource potential. Specifically, it investigates how economic education affects economic literacy and business diversification, and how it contributes to increasing community income.MethodThe research employed a mixed-methods approach, combining quantitative and qualitative data to provide a comprehensive analysis. Quantitative data were collected via a structured survey involving 300 respondents, while qualitative insights were obtained through in-depth interviews with 15 selected participants. Artificial Intelligence (AI) tools were used to assist in refining and analyzing the content for clarity and coherence.ResultsThe findings reveal that economic education significantly enhances economic literacy, as shown by an increase in literacy scores from 3.1 to 4.3. Moreover, 40% of respondents diversified their businesses after participating in the training—primarily into value-added agricultural products and tourism services. Interview data also highlight a shift in mindset, with communities beginning to focus on the development and management of local resources rather than merely utilizing them in traditional ways.ImplicationsThe study underscores the importance of practice-based economic education programs that incorporate technology and uphold Sharia principles. Effective collaboration among government institutions, private sectors, and educational bodies is essential to support infrastructure and funding for sustainable impact.Originality/NoveltyThis study uniquely combines the perspectives of economic education and Sharia entrepreneurship in the context of local resource optimization, an approach that has rarely been addressed in previous empirical studies. It also integrates AI-assisted analysis for enhanced validity and relevance in community development frameworks.